THE EFFECT OF CHAIN VALUE CREATION ON INCREASING THE FASHION INDUSTRY BUSINESS PERFORMANCE IN BANDUNG CITY - Syahyono, Syahyono (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The era of globalization causes increasingly competitive competition towards the creative economy. This creative economy is driven by an industrial sector called the creative industry. Creative industries that have optimal business performance are creative industries that apply value chains to each of their business processes. The value chain provides value delivery that offers superior value to the creative industries. However, this value chain is not owned or fully functional as it should be in the creative industry of the Binong Jati UMKM knitting center in Bandung. This article discusses aspects of business performance that are affected by value chain creation. This study uses descriptive-verificative survey research. The sampling technique used is probability random sampling. The results showed the influence of the value chain on business performance. So it can be concluded that the better the value chain, the higher the business performance at Binong Jati Knitting Center, Bandung City, and vice versa.